The Lure of Car Culture - Gender, Class and Nation in 21st Century Car Culture in China. - Christensen, Hilda Rømer (Kvinder, Køn & Forskning, 2015)
The aim of this article is to scrutinize car culture and gender in post-socialist China and to show how discourses of mobility and gender have come to be intertwined with the new middle class and ideas of nation and cars as imagined communities. The article departs from theoretical and methodological considerations of gender and car culture and argues that gender and cars are entangled in both global and local assemblages. Using China Daily as the main source of analysis, the article examines how dominant ideas of cars and gender have interfaced with the emerging Chinese middle class and new ideas of masculinity, femininity and Chineseness. Also the article locates car culture as a new site of cultivating individual senses, life styles and new moral aspects of social life. Present day urban car culture in China both challenges and radicalizes fixed figures of gendered and masculinised car culture; while at the same time carving out new gaps related to class, gender and more sustainable modes of transportation.